(untitled) (Medico Legal Update, 2019)
Training for little dentist turns into one of promotion efforts to empower the cadre. Meanwhile, the communication skills is expected to promote the importance of dental and oral health to others. This study aims to analyze the relationship between little dentist’s training towards their communication skills. The cross sectional research was done to the participant of little dentist’s training at Bina Sehat hospital, involved 82 children selected by purposive sampling. The variables were training and communication skills of little dentist cadre. Data were collected using checklist and questionnaire, then analyzed by Gamma correlation test. The most of repondents (86.59%) got high score dealing with the training. There was 42.68% respondents’score categorized as good, 54.88% as sufficient. The p-value of Gamma correlation was 0.000 (there was relationship between little dentists cadre’s training and their communication skills